Strategi Pembelajaran Berbasis Karakter Religius di Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan - Moh. Makinun Amien (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This study aims to discuss the religious character-based learning strategy which is a learning strategy as the first acceleration of values or morals for students, with this students can learn morals that are not limited to subjects.. The research method used is qualitative with a phenomenological approach. From the analysis conducted by the researcher, there are several strategies used, including; Cooperative Learning, Problem Based Learning Strategy, Direct Learning Strategy (Expository), Affective Learning Strategy, PAIKEM Learning Strategy. However, the researcher did not find the value of religious character in the problem-based strategy, only as part of the learning strategy implemented in the new class VII student dormitory. The inhibiting factor was if the students did not feel at home in the dormitory, the graduates do not continue to other fostered dormitories, lack of support from parents, the lack of concern for educators on the affective values of students who prioritized their cognitive abilities, while the supporting factors are that students feel at home and are active in the dormitory, what if the graduates of the student dormitory were has just continued his education in a fostered dormitory who was very concerned about religious character, additional support and motivation from parents, educatorsâ€™ concern for affective rather than cognitive values, and involvement of dormitory educators in formal institutions.Â Penelitian ini bertujuan membahas tentang strategi pembelajaran berbasis karakter religius yang merupakan sebuah strategi pembelajaran sebagai percepatan nilai atau akhlak yang pertama bagi peserta didik, dengan ini peseta didik bisa belajar akhlak tidak dibatasi mata pelajaran. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan fenomenologi. Dari analisis yang dilakukan peneliti terdapat beberapa strategi yang digunakan antara lain; Cooperative Learning, Strategi Pembelajaran Berbasis Masalah, Strategi Pembelajaran Langsung (Ekspositori), Strategi Pembelajaran Afektif, Strategi Pembelajaran PAIKEM. Namun peneliti tidak menemukan nilai karakter religius pada strategi berbasis masalah, hanya sebagai bagian dari strategi pembelajaran yang diterapkan di asrama santri baru kelas VII. Faktor penghambatnya apabila santri tidak kerasan di asrama, lulusannya tidak melanjutkan ke asrama binaan lain, kurang dukungan dari orang tua, kurangnya kepedulian pendidik pada nilai afektif santri lebih mengutamakan kognitifnya, Sedangkan faktor pendukung, santri kerasan dan aktif di asrama, apabila lulusan asrama santri baru melanjutkan pendidikannya di asrama binaan yang sangat peduli terhadap karakter religius, adanya dukungan dan motivasi tambahan dari orang tua, kepedulian pendidik terhadap nilai afektif daripada kognitif, dan keterlibatan pendidik asrama di lembaga formal.